HUBUNGAN STIGMA SOSIAL DENGAN MINAT PEMERIKSAAN IVA PADA WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS ASTAMBUL - Ima Dewi; Putri Yuliantie; Laurensia Yunita; Novita Dewi Iswandari (Malang Journal of Midwifery (MAJORY), 2026)
Cervical cancer remains a leading cause of death among women. Visual Inspection with Acetic Acid (VIA) is an effective and low-cost screening method; however, its utilization remains low due to social stigma. This study aimed to analyze the relationship between social stigma and interest in VIA screening among women of reproductive age in the Astambul Community Health Center area. An analytical cross-sectional design was used involving 63 respondents selected through quota sampling. Data were collected using an adapted Cancer Stigma Scale (CASS) questionnaire and a VIA screening interest questionnaire. Data were analyzed using univariate and bivariate analysis with Fisher’s Exact Test. The results showed that most respondents had moderate stigma (92.1%) and were not interested in VIA screening (55.6%). There was a significant relationship between social stigma and interest in VIA screening (p=0.041). Lower social stigma was associated with higher interest in VIA screening. Therefore, continuous health education is needed to reduce stigma and increase screening participation.